The Internalization of Religious Moderation Values in Islamic Religious Education: A Study at SD Darma Bangsa Bandar Lampung - Lutfiah Holifa Balkis; Muqowim Muqowim (-, 2026)
This study aims to analyze the process of internalizing religious moderation values through Islamic Religious Education (PAI) learning in a multireligious school environment. This research is motivated by the urgency of strengthening religious moderation in education as a response to increasing intolerance and social diversity. The study employs a qualitative approach with a field research design conducted in an elementary school characterized by a multireligious background. Data were collected through interviews, observations, and documentation, and analyzed using interactive data analysis techniques. The results indicate that the internalization of religious moderation values is carried out through integrated learning processes, teacher role modeling, habituation, and social interactions among students. The learning emphasizes values such as tolerance, moderation, and justice, which are reinforced by an inclusive school environment. The multireligious setting provides real social experiences that enable students to understand and practice these values in their daily lives. As a result, students demonstrate inclusive attitudes, empathy, mutual respect, and moderate religious behavior. This study highlights that Islamic Religious Education in a multireligious school plays a strategic role in shaping students’ character and promoting harmonious coexistence in a diverse society.